Distributional patterns of the South American Aterpini (Coleoptera: Curculionidae) - Morrone, Juan José (1996)
The 23 species of South American Aterpini, belonging to the genera Aegorhinus Erichson, Alastoropolus Kuschel, and Micropolus Kuschel, are distributed in four areas of endemism, namely, Central Chile, Maule, the Valdivian forest, and the Magellanic forest. Distributional patterns of these species follow two generalized tracks: one connecting Central Chile and Maule, and the other connecting Maule, the Valdivian forest, and the Magellanic foresto Due to its conflicting relationships, Maule is postulated as a node. Two alternative area cladograms are presented in order to account for its complex nature: one shows the sequence (Valdivian forest (Maule, Central Chile», whereas the second shows the sequence (Magellanic forest (Maule, Valdivian forest)). These patterns are similar to those found in the Rhytirrhinini, although Aterpini are absent from the Magellanic moorland and the Falkland Islands.